On optical sensing of surface roughness of flat and curved microplastics in water. (September 2020) - Asamoah, Benjamin O.; Roussey, Matthieu; Peiponen, Kai-Erik
Abstract: The growth of microplastic (MP) pollution is of increasing concern and represents a global challenge. In situ detection of these small particles is difficult because of their sizes, shapes, transparency or translucency, surface texture and ambient conditions. We propose and demonstrate the use of a prototype optical sensor to detect flat, nearly flat, curved and rough MPs prepared from commercial polyethylene terephthalate (PET) plastics and PET bottles in water. The prototype measures the specular reflection of a laser radiation incident on MPs, with a photodiode, and the transmitted laser speckle pattern, with a charge-coupled device (CCD) camera. The presence of the MPs as well as the optical surface roughness are determined from the specular reflection. Additionally, the so-called speckle contrast calculated from the speckle pattern, as a promising tool, is used to rank the rough MPs according to the different average surface roughness, to approximately twice the wavelength of the probing light. The novel application of laser speckle contrast and the optical roughness estimation allows the description of MP surface roughness in water. Moreover, in combination with earlier studies, these results, therefore, pave a way for the complete and a relatively easier description of MPs properties optical and also advances our step towards the development of simple and robust optical monitoring techniques for micro and nanoplastics in open and wastewater. Graphical abstract: Image 1 Highlights: Optical detection of microplastics in freshwater bodies. Influence of surface roughness on the detection of microplastics. Characterization of optical surface roughness of microplastics in water. Combining optical detection methods towards the development of a portable optical sensor. Toward the investigation of optical phenomena for the development of a multifunctional optical sensor for on-field screening of microplastics in the aquatic environment.